Analysis of altruistic and egoistic effects in transportation networks (Research, Society and Development, 2021)
Transport networks are fundamental infrastructure for the dynamics of large urban centers. These structures are subject to congestion, which have a strong social, economic and environmental impact. In this work, an agent-based simulation model was built in order to investigate how altruistic behavior in route selection can affect travel times and flow distribution in a transport network. Methods: OpenStreetMap open database was used to obtain the structure of the transport network. Complex network theory was used to perform the simulation and estimate the impacts of congestion. Simulating mobility flows, we analyzed how the agents' path selection criteria influence congestion levels, path lengths and travel times. Results: altruistic behavior significantly reduces the propagation of congestion and the formation of groupings of congested roads in the transport network, as well as reducing the average travel time between two points, but increasing the average distance traveled in a smaller proportion.